Heat shock influences the fatty acid composition of the muscle of the Antarctic fish Trematomus bernacchii. (August 2018) - Truzzi, C.; Illuminati, S.; Antonucci, M.; Scarponi, G.; Annibaldi, A.
Abstract: In the Ross Sea region (average temperature of −1.87 °C), shelf water warming up to +0.8-+1.4 °C is predicted by 2200, so there is an urgent need to understand how organisms can respond to rising temperatures. In this study, we analyzed the effect of a heat shock on the fatty acid (FAs) composition of muscle of the Antarctic teleost Trematomus bernacchii, caught in Terra Nova Bay (Ross Sea), and held in fish tanks at 0, +1 or +2 °C, for 1, 5 and 10 days. In general, heat shock produced, beyond a reduction in total lipid content correlated to the temperature, an increase in the percentage of saturated FAs, and a decrease in mono-unsaturated FAs; however, the level of poly-unsaturated FAs did not seem to directly correlate with temperature. Principal component analysis indicated that both temperature and exposure time affect the composition of FAs in the muscle probably through an alteration of the metabolic pathways of FAs. In this study, we demonstrated that T. bernacchii was capable to rapidly acclimatize to a heat shock. This study contributes to increasing knowledge on the effect of temperature on the lipid composition of T. bernacchii and is complementary to previous studies on the gene expression and biochemistry of this species face multiple stressors. Graphical abstract: Image 1 Highlights: Muscle of Trematomus. bernacchii : effect of heat shock on fatty acids (FA) levels. Temperature (0, +1, +2 °C) and exposure-time (1, 5, 10 days) influence both FA composition and lipid content. Heat shock: saturated- FA increase, mono-unsaturated FA decrease, poly-unsaturated FA variable response. From Principal Component Analysis we assume an alteration of metabolic pathways of FAs. Heat shock: modification of FA composition aimed at maintaining the proper fluidity of the membrane cell.